1996
DOI: 10.1101/lm.3.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of c-Fos in rat amygdala during training is required for encoding conditioned taste aversion memory.

Abstract: Local microinjection into rat amygdala of phosphorothioate modified oligodeoxynucleotides (ODNs) antisense to c-los several hours before conditioned taste aversion (CTA) training impaired taste aversion memory tested 3-5 days after conditioning. In contrast, injection of the antisense ODNs several days before training, before testing, or into the basal ganglia, or injection of c-fos sense ODNs, had no effect on CTA memory. Inhibition of translation by local microinjection of anisomycin into the amygdala shortl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
1
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 43 publications
5
99
1
2
Order By: Relevance
“…However, neither behavioral effects nor signs of structural damage were observed when amounts of c-fos AS-ODN comparable to those used in the present study were applied to the amygdala several days (i.e., with an interval that allows degradation of ODNs) before training or shortly before testing of rats in a conditioned taste aversion paradigm (Lamprecht and Dudai 1996). Similarly, in the present study no tissue damage additional to injuries caused by the insertion of cannulae was observed in ODN-treated versus saline-treated rats during determination of cannulae positions 5 days following intrahippocampal injections (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…However, neither behavioral effects nor signs of structural damage were observed when amounts of c-fos AS-ODN comparable to those used in the present study were applied to the amygdala several days (i.e., with an interval that allows degradation of ODNs) before training or shortly before testing of rats in a conditioned taste aversion paradigm (Lamprecht and Dudai 1996). Similarly, in the present study no tissue damage additional to injuries caused by the insertion of cannulae was observed in ODN-treated versus saline-treated rats during determination of cannulae positions 5 days following intrahippocampal injections (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Although the neural mechanisms underlying the robust and long-lasting association of taste aversion and nausea have yet to be elucidated, several brain areas have been implicated, including the amygdala and cortex. It has been shown that protein synthesis and new gene expression in the central amygdala are required for CTA memory (Lamprecht and Dudai, 1996). Furthermore, several studies have indicated that the amygdala CREB is essential for long-term CTA memory or for the retrieval of already formed long-term memory (Lamprecht et al, 1997;Balschun et al, 2003;Josselyn et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…S1] revealed robust induction of Arc mRNA in response to individual presentation of CS taste (0.5% saccharin solution) and US LiCl (0.15 M 15 ml/kg body weight, i.p.) in the insular cortex (IC) and basolateral nucleus of the amygdala (BLA), two regions believed to be involved in CTA acquisition (15)(16)(17)(18), leading us to focus on these regions for evidence of CS-US convergence.…”
mentioning
confidence: 99%